The Structural Model of Customer Loyalty Through Customer Satisfaction: A Case Study of Grab Bike in Manado City - Walean, Ronny H.; Makarawung, Reynard Justino (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Grab is a Singaporean online transportation company that is already present in the city of Manado. The main objective of this research is to analyze and determine the effect of service quality and brand trust as exogenous variables on customer loyalty through customer satisfaction as an endogenous variable. Data collection using a questionnaire with the Likert Scale method by taking the number of respondents, as many as 337 people. The type of research used is structural / pathway research with data analysis using the Structural Equation Modeling (SEM) method in the AMOS 21 program. The results of the analysis of this study are that both service quality and brand trust have a significant effect on customer satisfaction. Customer satisfaction has a significant effect on customer loyalty. The Sobel test shows that customer satisfaction variables can mediate service quality and brand trust on customer loyalty. Keywords : Customer loyalty, customer satisfaction, structural equation modeling (SEM), Grab-bike